Verifying the operation of an elastic crossbar system applied to a panel painting: the Deposition from the Cross by an anonymous artist from Abruzzo, sixteenth century. (3rd April 2017) - Cocchi, Linda; Marcon, Bertrand; Goli, Giacomo; Mazzanti, Paola; Castelli, Ciro; Santacesaria, Andrea; Uzielli, Luca
Abstract : This study deals with the post-treatment evaluation of the elastic crossbar system already designed and installed on the recently restored panel painting Deposition from the Cross by an anonymous artist from Abruzzo (sixteenth century). After the restoration, the panel and the crossbars were subjected to mechanical tests to identify their elastic characteristics. Then the panel, equipped with the elastic crossbar system, was subjected for about two months to controlled environmental cycles made up of approximately constant humidity periods. During the two months, the forces exerted by the springs and the deformations of both panel and crossbars were continuously monitored. A mathematical model, calibrated on the specific parameters derived from the analysis of the panel, provided the deformation that the panel would have shown without the crossbars; comparing the model output with the measured data provided a restraining effect (RE) of approximately 7% (RE could range between zero – no restraint – and 100% – total restraint). Future developments of this project will define appropriate procedures to design an elastic crossbar system for a given panel, once the expert judgement of restorers has identified the most desirable RE to be achieved.